A phosphorus-nitrogen flame-retardant dispersion, a flame-retardant cellulose fiber, and a method for producing the same

CN123005531APending Publication Date: 2026-10-30XIAN THERMAL POWER RES INST CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611165875.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-03
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0004]本发明提供了一种磷氮阻燃分散体、阻燃纤维素纤维及其制备方法,有效解决了阻燃剂易团聚堵塞喷丝孔及阻燃组分易迁移流失的技术难题,使制得的阻燃纤维素纤维兼具高阻燃效率、离火自熄特性及优异的阻燃耐久性

Benefits of technology

通过连续水相及分散于其中的核壳颗粒构成全水相阻燃分散体,以磷氮阻燃核提供阻燃来源,并利用吸附于其表面的聚胺内层作为中间联结层,使组装于聚胺内层表面的海藻酸盐外层在碱性纤维素纺丝原液中以水化负电形式稳定分散、有效抑制阻燃颗粒团聚和沉降,当进入含酸和二价金属离子的凝固浴时,海藻酸盐外层发生质子化收缩并与金属离子配位交联,同时聚胺内层发生质子化并与海藻酸盐外层形成离子缔合,使壳层原位致密化,实现阻燃组分随纤维素凝固再生的同步高效固定。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123005531A_ABST
    Figure CN123005531A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of flame retardation, and relates to a phosphorus-nitrogen flame-retardant dispersion, a flame-retardant cellulose fiber and a preparation method thereof. The phosphorus-nitrogen flame-retardant dispersion comprises a continuous water phase and core-shell particles dispersed in the continuous water phase; the core-shell particles comprise, from inside to outside, a phosphorus-nitrogen flame-retardant core, a polyamine inner layer adsorbed on the surface of the phosphorus-nitrogen flame-retardant core and a alginate outer layer assembled on the surface of the polyamine inner layer. The application constructs a core-shell structure of the phosphorus-nitrogen flame-retardant core-polyamine inner layer-alginate outer layer, uses the strong negative water layer of the alginate outer layer in an alkaline spinning dope to realize stable dispersion, and realizes in-situ densification of the shell layer by coordination crosslinking with divalent metal ions in an acid coagulation bath, thereby effectively solving the technical problems of easy agglomeration and blockage of the spinneret hole of the flame retardant and easy migration and loss of the flame-retardant component, and making the prepared flame-retardant cellulose fiber have high flame-retardant efficiency, a self-extinguishing characteristic and excellent flame-retardant durability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of flame retardant technology and relates to a phosphorus-nitrogen flame retardant dispersion, flame retardant cellulose fiber and its preparation method. Background Technology

[0002] Regenerated cellulose fibers have advantages such as good moisture absorption, comfortable wear, and renewable raw materials, making them one of the main types of chemical fibers. However, regenerated cellulose fibers have a low limiting oxygen index and are highly flammable, which limits their application in fields with high requirements for flame retardant performance, such as safety protection, vehicle interiors, and textiles for public places.

[0003] Currently, the main methods for imparting flame-retardant properties to regenerated cellulose fibers fall into two categories: blending and finishing. Blending involves directly adding the flame retardant to the cellulose spinning solution, allowing the flame-retardant component to co-coagulate with the cellulose. However, when flame-retardant powder is directly mixed with the spinning solution, the high viscosity of the cellulose spinning solution causes the powder to easily agglomerate and settle, making uniform dispersion difficult and leading to spinneret blockage and a decrease in fiber mechanical properties. Although the flame retardant can be pre-dispersed into a suspension before being added to the spinning solution to improve dispersibility, the dispersants and other auxiliaries used will enter the coagulation bath, affecting solvent recovery and increasing costs. The auxiliaries remaining in the fiber can also affect fiber performance. More importantly, during coagulation and subsequent washing, the flame retardant in flame-retardant fibers prepared by blending tends to migrate outwards, resulting in low retention of the flame-retardant component and insufficient flame-retardant durability. Post-finishing methods involve applying flame-retardant finishing to already formed cellulose fibers. Common methods include surface grafting, padding-drying-baking, and layer-by-layer self-assembly. These methods generally suffer from problems such as low grafting efficiency, high cost, deterioration of fiber feel, and lack of durability of flame-retardant effect, making it difficult to achieve long-lasting flame-retardant effect while maintaining the original excellent properties of the fiber. Summary of the Invention

[0004] This invention provides a phosphorus-nitrogen flame retardant dispersion, flame retardant cellulose fiber, and its preparation method, which effectively solves the technical problems of flame retardant easily agglomerating and clogging spinneret orifices and flame retardant components easily migrating and being lost. The resulting flame retardant cellulose fiber has high flame retardant efficiency, self-extinguishing properties, and excellent flame retardant durability.

[0005] To achieve the above objectives, the present invention employs the following technical solution: In a first aspect, the present invention provides a phosphorus-nitrogen flame retardant dispersion comprising a continuous aqueous phase and core-shell particles dispersed in the continuous aqueous phase; the core-shell particles, from the inside out, comprise a phosphorus-nitrogen flame retardant core, a polyamine inner layer adsorbed on the surface of the phosphorus-nitrogen flame retardant core, and an alginate outer layer assembled on the surface of the polyamine inner layer.

[0006] Preferably, the mass ratio of the phosphorus-nitrogen flame-retardant core, the polyamine inner layer, and the alginate outer layer is 100:(0.5~8):(1~15).

[0007] Preferably, the material of the phosphorus-nitrogen flame retardant core is melamine polyphosphate, ammonium polyphosphate, melamine phosphate, or ammonium polyphosphate compounded on the surface of melamine; Alternatively, the material of the phosphorus-nitrogen flame-retardant core may be melamine polyphosphate, ammonium polyphosphate, melamine phosphate, or a composite particle formed by ammonium polyphosphate compounded on the surface of melamine and phosphorus-containing inorganic sheet material.

[0008] Preferably, the material of the polyamine inner layer includes one or more of branched polyethyleneimine, linear polyethyleneimine, polyallylamine, and polyamide amine; Alternatively, the material of the inner polyamine layer may be a water-soluble salt of branched polyethyleneimine, linear polyethyleneimine, polyallylamine, or polyamide amine.

[0009] Preferably, the material of the alginate outer shell layer is one or more of sodium alginate and potassium alginate.

[0010] Secondly, the present invention provides a method for preparing a phosphorus-nitrogen flame retardant dispersion, comprising the following steps: The phosphorus-nitrogen flame retardant material, water and dispersant stabilizer are mixed and then subjected to wet grinding or high-pressure homogenization at 5~35℃ to obtain a flame retardant core dispersion containing phosphorus-nitrogen flame retardant cores. The pH of the flame-retardant core dispersion is adjusted to 8.0~10.5, and a polyamine aqueous solution is added under stirring. Stirring is continued to allow the polyamine to be adsorbed onto the surface of the phosphorus-nitrogen flame-retardant material, forming a flame-retardant core dispersion with a polyamine inner layer. The pH of the flame-retardant core dispersion with the polyamine inner layer is maintained at 8.0~11.0. Under shear conditions, an aqueous alginate solution is added, and stirring is continued to allow the alginate to assemble on the surface of the polyamine inner layer, forming the phosphorus-nitrogen flame-retardant dispersion.

[0011] Preferably, the dispersant stabilizer includes one or more of polyvinylpyrrolidone and polyoxyethylene ether nonionic dispersants.

[0012] Preferably, the amount of the dispersing stabilizer is 0.1% to 3% of the mass of the phosphorus-nitrogen flame retardant material.

[0013] Thirdly, the present invention provides a method for preparing flame-retardant cellulose fibers, comprising the following steps: The phosphorus-nitrogen flame retardant dispersion according to any one of claims 1 to 5 is mixed with an alkaline cellulose spinning solution to obtain a flame retardant spinning solution; The flame-retardant spinning solution is extruded into a coagulation bath containing acid and divalent metal ions, so that the cellulose in the alkaline cellulose spinning solution is coagulated and regenerated to obtain nascent fibers. The nascent fibers are stretched, washed, and dried to obtain flame-retardant cellulose fibers.

[0014] Fourthly, the present invention provides a flame-retardant cellulose fiber.

[0015] Compared with the prior art, the present invention has the following beneficial effects: A full-aqueous flame-retardant dispersion is constructed by a continuous aqueous phase and core-shell particles dispersed therein. The flame retardant source is provided by the phosphorus and nitrogen flame-retardant core, and the polyamine inner layer adsorbed on its surface is used as an intermediate connecting layer. The alginate outer layer assembled on the surface of the polyamine inner layer is stably dispersed in the alkaline cellulose spinning solution in the form of hydration and negative charge, which effectively inhibits the agglomeration and sedimentation of flame-retardant particles. When it enters the coagulation bath containing acid and divalent metal ions, the alginate outer layer undergoes protonation and shrinkage and coordinates and crosslinks with the metal ions. At the same time, the polyamine inner layer undergoes protonation and forms ion association with the alginate outer layer, which makes the shell layer denser in situ, realizing the synchronous and efficient fixation of flame-retardant components with the coagulation and regeneration of cellulose. Attached Figure Description

[0016] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.

[0017] Figure 1 This is a schematic diagram illustrating the state changes at the core-shell particle interface. Detailed Implementation

[0018] To enable those skilled in the art to understand the features and effects of the present invention, the terms and expressions used in the specification and claims are explained and defined in general below. Unless otherwise specified, all technical and scientific terms used herein have the ordinary meaning understood by those skilled in the art regarding the present invention, and in case of conflict, the definitions in this specification shall prevail.

[0019] The theories or mechanisms described and disclosed herein, whether right or wrong, should not in any way limit the scope of the invention, that is, the contents of the invention can be implemented without being limited by any particular theory or mechanism.

[0020] In this document, all features defined by numerical ranges or percentage ranges, such as numerical values, quantities, contents, and concentrations, are for the sake of brevity and convenience only. Accordingly, descriptions of numerical ranges or percentage ranges should be considered as covering and specifically disclosing all possible sub-ranges and individual numerical values ​​(including integers and fractions) within those ranges.

[0021] In this article, unless otherwise specified, “contains,” “includes,” “containing,” “has,” or similar terms cover the meanings of “composed of” and “mainly composed of,” for example, “A contains a” covers the meanings of “A contains a and others” and “A contains only a.”

[0022] For the sake of brevity, not all possible combinations of the technical features in each implementation scheme or embodiment are described herein. Therefore, as long as there is no contradiction in the combination of these technical features, the technical features in each implementation scheme or embodiment can be combined arbitrarily, and all possible combinations should be considered within the scope of this specification.

[0023] The present invention will now be described in further detail with reference to the accompanying drawings: The first objective of this invention is to provide a phosphorus-nitrogen flame retardant dispersion comprising a continuous aqueous phase and core-shell particles dispersed in the continuous aqueous phase; the core-shell particles, from the inside out, comprise a phosphorus-nitrogen flame retardant core, a polyamine inner layer adsorbed on the surface of the phosphorus-nitrogen flame retardant core, and an alginate outer layer assembled on the surface of the polyamine inner layer.

[0024] Specifically, the core-shell particles have a phosphorus-nitrogen flame-retardant core as the innermost layer, serving as the acid and gas source core of the intumescent flame-retardant system. When heated, it promotes the directional dehydration of cellulose into char and releases diluent gases. The middle polyamine inner layer remains non-ionic in the alkaline spinning solution to maintain core layer stability and rapidly protonates into a cationic polyelectrolyte upon entering the acidic coagulation bath. The outermost alginate outer layer utilizes the full ionization of its carboxyl groups under alkaline conditions to form a strongly negatively charged hydration layer. This allows the particles to maintain a monodisperse state in the cellulose forming solution for a long time due to electrostatic repulsion and steric hindrance, fundamentally solving the engineering problem of traditional flame retardants easily agglomerating and clogging spinnerets. Figure 1As shown, when the spinning solution enters the coagulation bath containing acid and divalent metal ions, the outer layer of alginate undergoes protonation-induced segment collapse and contraction. Simultaneously, divalent metal ions (such as zinc and calcium) form coordination crosslinks between adjacent carboxyl groups, further densifying the shell. At the same time, the protonated polyamine inner layer undergoes strong ionic association with the alginate anionic segments, forming additional crosslinking anchors between the inner and outer layers. These three factors synergistically promote the in-situ transformation of the swollen polyelectrolyte shell into a tough and dense interfacial barrier. This barrier, on the one hand, firmly fixes the flame-retardant core into the regenerating cellulose matrix through physical interlocking and interfacial bonding, effectively inhibiting the migration of flame-retardant components into the coagulation bath and subsequent washing media, ensuring high retention. On the other hand, during combustion, the alginate-metal ion coordination structure synergistically promotes the formation of a continuous and structurally complete expanded char layer with phosphorus and nitrogen flame-retardant cores, significantly improving flame-retardant efficiency while also maintaining fiber mechanical properties.

[0025] The phosphorus-nitrogen flame-retardant dispersion has a solid content of 5wt%~35wt%, ensuring sufficient loading of the flame-retardant active ingredients, avoiding excessive dilution of the spinning solution, and preventing a sudden increase in viscosity and particle aggregation caused by excessive solid content. Simultaneously, the pH is maintained at 8.5~11.5. This alkaline range allows for sufficient ionization of the outer carboxyl groups of alginate to generate a dense negative charge, while also ensuring good compatibility with the alkaline environment of the cellulose forming solution itself, preventing damage to the interfacial structure of the core-shell particles due to sudden pH changes. The zeta potential measured under the target spinning solution dilution conditions is ≤ At 20mV, from a colloidal chemistry perspective, the particles maintain a sufficient electrostatic repulsion barrier in complex spinning media, effectively suppressing problems such as agglomeration, sedimentation, and increased filtration pressure difference.

[0026] For example, the median particle size D50 of the phosphorus-nitrogen flame retardant core is 0.05~0.8μm. This range avoids the agglomeration of excessively fine particles due to high surface energy and the resulting increase in grinding costs, while also preventing excessively coarse particles from settling too quickly and having insufficient specific surface area, thus reducing flame retardant efficiency. This ensures a balance between dispersion stability and flame retardant activity. At the same time, limiting D90 to no more than 2.0μm eliminates the presence of large particles from the tail end of the particle size distribution, effectively reducing the risk of spinneret blockage and stress concentration within the fiber. This allows the flame retardant core to be evenly distributed across the fiber cross-section, providing a particle-level guarantee for balancing spinnability, flame retardant efficiency, and fiber mechanical properties.

[0027] For example, the mass ratio of the phosphorus-nitrogen flame-retardant core, the polyamine inner layer, and the alginate outer layer is 100:(0.5~8):(1~15), and more preferably 100:(1~5):(2~10). Within this range, polyamine and alginate form a structurally regular composite shell through electrostatic assembly, which takes into account the dispersion stability in alkaline spinning solution, the rapid response densification in acidic coagulation bath, and the sufficient proportion of flame-retardant core in fiber, thereby achieving the optimal match between spinnability, flame retardant efficiency, and fixation effect.

[0028] For example, the present invention selects melamine polyphosphate, ammonium polyphosphate, melamine phosphate, or ammonium polyphosphate compounded on the surface of melamine as the material of phosphorus-nitrogen flame retardant core. Such materials have the dual functions of phosphorus source and nitrogen source. When heated, the phosphorus component catalyzes the dehydration of cellulose to form char, and the nitrogen component releases non-flammable gas to dilute flammable volatiles. The two work together to form a typical intumescent flame retardant system, and have low solubility and good chemical stability in aqueous medium, which can be compatible with the subsequent adsorption process of polyamine inner layer. In addition, the above materials can be combined with phosphorus-containing inorganic sheet materials (such as zirconium phosphate, layered bimetallic hydroxide, etc.) to form composite particles. The physical barrier effect and synergistic flame retardant effect of the sheet material can be used to further improve the char density. At the same time, the abundant hydroxyl groups on the surface of the sheet structure can provide more adsorption sites for polyamine, which helps to strengthen the anchoring effect of polyamine inner layer.

[0029] For example, the present invention selects branched polyethyleneimine, linear polyethyleneimine, polyallylamine, polyamide amine, or their water-soluble salts as the material of the polyamine inner layer. The molecular chains of these polyamines are rich in primary, secondary, or tertiary amine groups, which can be firmly adsorbed onto the surface of the phosphorus and nitrogen flame retardant core in the aqueous phase through electrostatic attraction, hydrogen bonding, and coordination to form a uniform and stable organic coating layer. Its weight-average molecular weight is limited to 1,000 to 100,000. When the molecular weight is less than 1,000, the chain segments are too short and the anchoring points provided by a single molecule are insufficient, making it difficult to form a continuous coverage on the flame retardant core surface and easy to be washed away. When the molecular weight is greater than 100,000, the molecular chains are too long and the steric hindrance is significant, which not only reduces the adsorption amount of polyamine per unit mass but also easily causes bridging and flocculation between particles. At the same time, the high viscosity also makes it difficult for subsequent ultrafiltration to remove free polyamine.

[0030] For example, this invention uses one or more of sodium alginate and potassium alginate as the material for the alginate shell layer. These natural polysaccharides are rich in carboxyl groups, exhibiting good water solubility and biocompatibility in aqueous solutions. Furthermore, their carboxyl groups, after being fully ionized under alkaline conditions, can provide a strong negatively charged repulsive force to the core-shell particles, making them an ideal choice for constructing the shell layer of aqueous dispersions. The apparent viscosity-average molecular weight of alginate is limited to 30,000–500,000. When the molecular weight is below 30,000, the chain segments are too short, the assembly layer density is insufficient, and the crosslinking sites are limited, making it difficult to... In an acidic coagulation bath, a sufficiently tough and dense shell is formed. However, when the molecular chain is higher than 500,000, the molecular chain becomes too long, resulting in a high viscosity of the aqueous solution. This not only increases the difficulty of operation but may also make the shell too thick, thus weakening the mass ratio of the flame-retardant core. The M / G ratio (the ratio of mannuronic acid to guluronic acid segments) is controlled between 0.3 and 2.5. When the G segment content is higher, the chain segments are more rigid and have better coordination selectivity with divalent metal ions, which is conducive to the formation of a high-strength cross-linked structure. When the M segment content is higher, the chain segments have better flexibility, which helps to achieve uniform coating on the surface of the flame-retardant core.

[0031] A second objective of this invention is to provide a method for preparing a phosphorus-nitrogen flame retardant dispersion, comprising the following steps: Phosphorus-nitrogen flame retardant material, water, and dispersant stabilizer are mixed and then wet-milled or homogenized under high pressure at 5-35°C to obtain a flame retardant core dispersion containing phosphorus-nitrogen flame retardant cores. This temperature range avoids overheating of the material during milling, which could cause changes in the surface properties of the particles, while ensuring good fluidity of the aqueous system. The dispersant stabilizer is selected from polyvinylpyrrolidone or polyoxyethylene ether nonionic dispersants, and its dosage is 0.1% to 3% of the mass of phosphorus-nitrogen flame retardant material. The steric hindrance effect of nonionic dispersants effectively inhibits the re-agglomeration of newly formed particles after refining, while avoiding the interference that ionic dispersants may cause to the subsequent electrostatic adsorption of polyamine. The pH of the flame-retardant core dispersion is adjusted to 8.0~10.5. Under this alkaline condition, the amine groups on the polyamine molecular chain mainly exist in the form of non-protonated groups, which is conducive to uniform adsorption on the flame-retardant core surface through hydrogen bonding and surface coordination. After removing free polyamine by centrifugation or ultrafiltration, a flame-retardant core dispersion with a polyamine inner layer is formed. The pH of the flame-retardant core dispersion with the polyamine inner layer is maintained at 8.0~11.0. Under shear conditions, an aqueous alginate solution is added, allowing the alginate to self-assemble on the surface of the polyamine inner layer through electrostatic interaction. This pH range ensures high ionization of the alginate carboxyl groups to drive the assembly process, while avoiding excessive shear force that could damage the formed core-shell structure, thus forming the phosphorus-nitrogen flame-retardant dispersion.

[0032] A third objective of this invention is to provide a method for preparing flame-retardant cellulose fibers, characterized by comprising the following steps: The above phosphorus-nitrogen flame retardant dispersion is mixed with alkaline cellulose spinning solution and then degassed and filtered to obtain flame retardant spinning solution. For example, based on 100 parts of oven-dry cellulose, the amount of phosphorus-nitrogen flame retardant core added is 5 to 30 parts. Within this range, a good balance between flame retardant efficiency and spinnability can be ensured. Moreover, the D90 of the phosphorus-nitrogen flame retardant core must be less than one-tenth of the minimum effective diameter of the spinneret. This particle size constraint fully ensures that the particles will not be physically blocked or accumulate at the orifice when flowing through the spinneret micro-orifice, which is a basic prerequisite for ensuring long-term continuous spinning operation. The obtained flame-retardant spinning solution was extruded into a coagulation bath containing acids and divalent metal ions (such as sulfuric acid, sodium sulfate, and zinc sulfate). The cellulose in the viscose spinning solution rapidly coagulated and regenerated in the acidic medium. Simultaneously, the outer layer of alginate underwent chain segment collapse and shrinkage due to carboxylation, and the Zn in the coagulation bath… 2+ or Ca 2+Divalent metal ions form coordination crosslinks between adjacent alginate carboxyl groups. After the polyamine inner layer is protonated under acidic conditions, it generates strong ion association with the alginate anionic chain. The synergistic effect of the inner and outer layers promotes in-situ densification of the shell layer of the core-shell particles within the same time window of cellulose formation. The nascent fibers are then stretched, washed, and dried to obtain flame-retardant cellulose fibers in which the flame-retardant components are evenly distributed within the fibers.

[0033] The fourth objective of this invention is to provide a flame-retardant cellulose fiber in which core-shell particles are dispersed in an intact form and firmly fixed inside the fiber, rather than merely adhering to the fiber surface. Unlike traditional flame-retardant fibers where flame retardants are often lost in large quantities during coagulation and washing, or only accumulate on the fiber surface with insufficient content inside, the core-shell particles of this invention achieve in-situ densification of the shell layer during the coagulation stage through a dual triggering effect of acid and divalent metal ions. This physically locks the core-shell particles within the regenerating cellulose matrix. During subsequent washing, the dense shell layer effectively inhibits the outward migration of the flame-retardant core, ensuring the flame-retardant components remain within the fiber. The cross-sectional direction exhibits a uniform distribution from the surface inwards. Simultaneously, the polyamine inner layer and the alginate outer layer can synergistically participate in the char formation reaction during combustion heating. The coordination structure formed by alginate and metal ions helps to improve the thermal stability and density of the char layer. Together with the phosphorus and nitrogen flame-retardant core, they constitute a synergistic intumescent flame-retardant system, enabling the fiber to rapidly form a continuous, dense, and sufficiently strong intumescent char layer when heated to block heat and mass transfer. The final product combines excellent flame-retardant performance and flame-retardant durability, making it suitable for applications requiring long-term flame-retardant safety, such as protective clothing, vehicle interiors, and textiles for public places.

[0034] The present invention will be further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Furthermore, it should be understood that after reading the teachings of this invention, those skilled in the art can make various alterations or modifications to the invention, and these equivalent forms also fall within the scope defined by the appended claims.

[0035] The following examples use instruments and equipment conventional in the art. Experimental methods in the following examples, unless otherwise specified, are generally performed under conventional conditions or as recommended by the manufacturer. All raw materials used in the following examples are conventional commercially available products with specifications conventional in the art. In this specification and the following examples, unless otherwise specified, "%" refers to weight percentage, "parts" refers to parts by weight, and "ratio" refers to weight proportion.

[0036] Example 1 Step 1: Preparation of the phosphorus-nitrogen flame-retardant core dispersion: Weigh 100 parts by mass of melamine polyphosphate, 200 parts by mass of deionized water, and 1 part by mass of polyvinylpyrrolidone. Dissolve the polyvinylpyrrolidone in the deionized water beforehand, and then add the melamine polyphosphate in batches while stirring. After the addition is complete, continue pre-dispersing for 30 minutes to form a uniform slurry. Feed the slurry into a wet grinding equipment and grind it under circulating cooling conditions, controlling the material temperature at 25±5℃, until the particle size D50 is 0.1~0.5μm and D90 is not greater than 1.5μm, thus obtaining the phosphorus-nitrogen flame-retardant core dispersion.

[0037] Step 2, Construction of the polyamine inner layer: Adjust the pH of the phosphorus-nitrogen flame-retardant core dispersion to 9.0±0.2 using a dilute sodium hydroxide aqueous solution. Prepare a 10% (w / w) polyethyleneimine aqueous solution with 3 parts by mass of branched polyethyleneimine, and add it dropwise to the phosphorus-nitrogen flame-retardant core dispersion over 20-30 minutes under stirring at 500-800 rpm. Maintain the system temperature at 20-25℃ and the pH at 8.8-9.2 during the dropwise addition. After the dropwise addition is complete, continue stirring for 60 minutes to allow the branched polyethyleneimine to adsorb onto the surface of the melamine polyphosphate particles.

[0038] Step 3, Removal of Free Polyamine: The dispersion obtained in Step 2 is introduced into an ultrafiltration device and ultrafiltration is performed using an ultrafiltration membrane with a molecular weight cutoff of 30 kDa. During the ultrafiltration process, deionized water is added for washing until the content of free polyethyleneimine in the permeate no longer changes significantly. The ultrafiltration retentate is collected, and its solid content is adjusted to give it the fluidity required for subsequent interfacial assembly, resulting in a flame-retardant core dispersion with a polyamine inner layer.

[0039] Step 4, Construction of the Alginate Outer Layer: Weigh 6 parts by mass of sodium alginate and add it to deionized water. Stir at room temperature until completely dissolved to prepare a 2% sodium alginate aqueous solution. Adjust the pH of the dispersion obtained in Step 3 to 9.5 ± 0.3. Under shear stirring conditions of 800-1200 r / min, slowly add the sodium alginate aqueous solution over 30-60 min. Avoid excessively high local concentrations of sodium alginate during the addition process. After the addition is complete, adjust the stirring speed to 400-600 r / min and continue stirring for 90 min to allow the sodium alginate to assemble onto the surface of the polyamine inner layer, obtaining a phosphorus-nitrogen flame-retardant dispersion. According to the subsequent spinning requirements, adjust the solid content and flowability of the dispersion with deionized water and control its pH at 9.0-10.0.

[0040] Step 5, Compounding of the Dispersion and Viscose Forming Solution: After the viscose forming solution has matured and before the final filtration, add the phosphorus-nitrogen flame-retardant dispersion obtained in Step 4. Based on 100 parts by weight of the oven-dry cellulose in the viscose forming solution, the amount of phosphorus-nitrogen flame-retardant core added is 15 parts by weight. During the addition process, maintain the viscose forming solution at 20-25°C. First, add the phosphorus-nitrogen flame-retardant dispersion continuously at a low flow rate, then stir and mix for 60 minutes to ensure the core-shell particles are uniformly dispersed in the viscose forming solution. After mixing, perform vacuum degassing and filter through the final filtration device to obtain the flame-retardant viscose spinning solution.

[0041] Step Six, Wet Forming: The flame-retardant viscose spinning solution is extruded into a coagulation bath through a spinneret. The coagulation bath contains 100 g / L sulfuric acid, 300 g / L sodium sulfate, and 10 g / L zinc sulfate, and the temperature is maintained at 45 ± 2℃. After the flame-retardant viscose spinning solution enters the coagulation bath, the viscose coagulates and the cellulose regenerates. Simultaneously, the outer layer of sodium alginate undergoes protonation shrinkage and reacts with Zn²⁺. + Coordination crosslinking occurs. The coagulated nascent fibers are stretched, then washed, desulfurized, washed again, and dried sequentially to obtain flame-retardant cellulose fibers.

[0042] Example 2 Step 1: Weigh 100 parts by weight of melamine polyphosphate, 200 parts by weight of deionized water, and 1 part by weight of polyvinylpyrrolidone. First, dissolve the polyvinylpyrrolidone in the deionized water, then add the melamine polyphosphate, pre-disperse for 30 minutes, and then perform wet grinding. During the grinding process, control the material temperature at 25±5℃ until the particle D50 is 0.1~0.5μm and D90 is no greater than 1.5μm, to obtain a phosphorus-nitrogen flame retardant core dispersion.

[0043] Step 2: Adjust the pH of the obtained phosphorus-nitrogen flame retardant core dispersion to 9.0 ± 0.2 using a dilute sodium hydroxide aqueous solution. Weigh 1 part by mass of branched polyethyleneimine and prepare a 5% aqueous solution; add it dropwise to the phosphorus-nitrogen flame retardant core dispersion over 20 minutes while stirring at 500-800 rpm. After the addition is complete, continue stirring at 20-25°C for 60 minutes to allow the branched polyethyleneimine to adsorb onto the surface of the phosphorus-nitrogen flame retardant core.

[0044] Step 3: The dispersion obtained in Step 2 is subjected to ultrafiltration and washing using an ultrafiltration membrane with a molecular weight cutoff of 30 kDa to remove unadsorbed free polyethyleneimine and collect the ultrafiltration retentate containing the polyamine-coated flame-retardant core.

[0045] Step four: Prepare a 2% (w / w) aqueous solution from 6 parts by mass of sodium alginate. Maintain the pH of the ultrafiltration retentate obtained in step three at 9.0–10.0, and add the sodium alginate aqueous solution over 30–60 minutes under shear stirring conditions of 800–1200 rpm. After the addition is complete, continue stirring for 90 minutes, and then adjust the solid content and flowability with deionized water to obtain a phosphorus-nitrogen flame retardant dispersion with a mass ratio of 100:1:6 for the phosphorus-nitrogen flame retardant core, polyamine inner layer, and alginate outer layer.

[0046] Step 5: After the viscose forming solution has matured and before the final filtration, add the phosphorus-nitrogen flame retardant dispersion obtained in Step 4. Based on 100 parts by weight of oven-dry cellulose, the amount of phosphorus-nitrogen flame retardant core added is 15 parts by weight. Stir and mix at 20-25°C for 60 minutes, followed by vacuum degassing and final filtration to obtain the flame-retardant viscose spinning solution.

[0047] Step six: The flame-retardant viscose spinning solution is extruded through a spinneret into a coagulation bath at a temperature of 45±2℃. The coagulation bath contains 100g / L sulfuric acid, 300g / L sodium sulfate, and 10g / L zinc sulfate. The nascent fibers formed by coagulation are then subjected to stretching, washing, desulfurization, re-washing, and drying to obtain flame-retardant cellulose fibers.

[0048] Example 3 Step 1: Mix 100 parts by weight of melamine polyphosphate, 200 parts by weight of deionized water, and 1 part by weight of polyvinylpyrrolidone. After pre-dispersing for 30 minutes, perform wet grinding. During grinding, use a circulating cooling method to control the material temperature at 25±5℃. Grind until the particle size D50 is 0.1~0.5μm and D90 is no greater than 1.5μm to obtain a phosphorus-nitrogen flame retardant core dispersion.

[0049] Step 2: Adjust the pH of the phosphorus-nitrogen flame retardant core dispersion to 9.0 ± 0.2. Weigh 3 parts by mass of branched polyethyleneimine and prepare a 10% aqueous solution. Add the solution dropwise to the phosphorus-nitrogen flame retardant core dispersion over 20 to 30 minutes while stirring at 500-800 rpm. After the addition is complete, continue stirring for 60 minutes to form the polyamine inner layer.

[0050] Step 3: Ultrafiltration is performed using an ultrafiltration membrane with a molecular weight cutoff of 30 kDa. Deionized water is added during the ultrafiltration process for washing to remove unadsorbed free polyethyleneimine. The ultrafiltration retentate is collected and its pH is adjusted to 9.5 ± 0.3.

[0051] Step 4: Weigh 10 parts by mass of sodium alginate and add it to deionized water to prepare a 2% sodium alginate aqueous solution. Under shear stirring conditions of 1000-1500 r / min, uniformly add the sodium alginate aqueous solution to the ultrafiltration retentate obtained in Step 3 over 45-60 min. After the addition is complete, reduce the stirring speed to 400-600 r / min and continue stirring for 120 min to allow the sodium alginate to complete the assembly on the surface of the polyamine inner layer, resulting in a phosphorus-nitrogen flame-retardant dispersion with a mass ratio of 100:3:10 for the phosphorus-nitrogen flame-retardant core, polyamine inner layer, and alginate outer layer.

[0052] Step 5: After the viscose forming solution has matured and before the final filtration, add the obtained phosphorus-nitrogen flame retardant dispersion. Based on 100 parts by weight of oven-dry cellulose, the amount of phosphorus-nitrogen flame retardant core added is 15 parts by weight. Control the system temperature at 20~25℃, stir and mix for 90 minutes, and after compounding, perform vacuum degassing and final filtration to obtain the flame-retardant viscose spinning solution.

[0053] Step Six: The flame-retardant viscose spinning solution is extruded through a spinneret into a coagulation bath containing 100 g / L sulfuric acid, 300 g / L sodium sulfate, and 10 g / L zinc sulfate. The coagulation bath temperature is 45 ± 2℃. The nascent fibers formed by coagulation are then drawn, followed by sequential washing, desulfurization, re-washing, and drying to obtain flame-retardant cellulose fibers.

[0054] Example 4 Step 1: 100 parts by weight of melamine polyphosphate, 200 parts by weight of deionized water, and 1 part by weight of polyvinylpyrrolidone are added sequentially to a dispersion container and stirred for pre-dispersion for 30 minutes. The resulting slurry is then wet-milled, and the material temperature is controlled at 25±5℃ by circulating cooling. The milling continues until the particle size D50 is 0.1~0.5μm and D90 is no greater than 1.5μm, yielding a phosphorus-nitrogen flame-retardant core dispersion.

[0055] Step 2: Adjust the pH of the phosphorus-nitrogen flame retardant core dispersion to 9.0 ± 0.2. Prepare a 10% aqueous solution of 3 parts by mass of branched polyethyleneimine. Slowly add the solution to the phosphorus-nitrogen flame retardant core dispersion over 20 to 30 minutes while stirring at 500 to 800 rpm. After the addition is complete, continue stirring at 20 to 25°C for 60 minutes.

[0056] Step 3: The dispersion obtained in Step 2 is subjected to ultrafiltration and washing through an ultrafiltration membrane with a molecular weight cutoff of 30 kDa to remove unadsorbed free polyethyleneimine. The ultrafiltration retentate is collected and its pH is adjusted to 9.5 ± 0.3.

[0057] Step four: Weigh 6 parts by mass of sodium alginate with an M / G ratio of 1.5, add it to deionized water, and stir thoroughly at room temperature to prepare a 2% sodium alginate aqueous solution. Under shear stirring conditions of 800-1200 r / min, add the sodium alginate aqueous solution to the ultrafiltration retentate obtained in step three over 30-60 min; after the addition is complete, continue stirring for 90 min to allow the sodium alginate to assemble on the inner surface of the polyamine. Subsequently, adjust the solid content and flowability of the dispersion with deionized water and control the pH at 9.0-10.0 to obtain a phosphorus-nitrogen flame retardant dispersion.

[0058] Step 5: After the viscose forming solution has matured and before the final filtration, add the phosphorus-nitrogen flame retardant dispersion obtained in Step 4. Based on 100 parts by weight of oven-dry cellulose, the amount of phosphorus-nitrogen flame retardant core added is 15 parts by weight. Maintain the system at 20-25℃ and stir for 60 minutes. After mixing, perform vacuum degassing and final filtration to obtain the flame-retardant viscose spinning solution.

[0059] Step six: The obtained flame-retardant viscose spinning solution is extruded through a spinneret into a coagulation bath at a temperature of 45±2℃. The coagulation bath contains 100g / L sulfuric acid, 300g / L sodium sulfate, and 10g / L zinc sulfate. After coagulation, the nascent fibers are drawn, then sequentially washed, desulfurized, washed again, and dried to obtain flame-retardant cellulose fibers.

[0060] Example 5 Step 1: Preparation of the phosphorus-nitrogen flame retardant core dispersion: Weigh 100 parts by mass of ammonium polyphosphate, 200 parts by mass of deionized water, and 0.1 parts by mass of polyvinylpyrrolidone. Dissolve the polyvinylpyrrolidone in the deionized water beforehand, and then add the ammonium polyphosphate in batches while stirring. After the addition is complete, continue pre-dispersing for 30 minutes to form a uniform slurry. Feed the slurry into a wet grinding equipment and grind it under circulating cooling conditions, controlling the material temperature at 25±5℃, until the particle size D50 is 0.1~0.5μm and D90 is not greater than 1.5μm, thus obtaining the phosphorus-nitrogen flame retardant core dispersion.

[0061] Step 2, Construction of the polyamine inner layer: Adjust the pH of the phosphorus-nitrogen flame retardant core dispersion to 9.0±0.2 using a dilute sodium hydroxide aqueous solution. Prepare a 5% (w / w) polyethyleneimine aqueous solution by dissolving 0.5 parts by mass of linear polyethyleneimine (weight average molecular weight approximately 10,000). Add the solution dropwise to the phosphorus-nitrogen flame retardant core dispersion over 20-30 minutes while stirring at 500-800 rpm. Maintain the system temperature at 20-25℃ and the pH at 8.8-9.2 during the dropwise addition. After the dropwise addition is complete, continue stirring for 60 minutes to allow the linear polyethyleneimine to adsorb onto the surface of the ammonium polyphosphate particles.

[0062] Step 3, Removal of Free Polyamine: The dispersion obtained in Step 2 is introduced into an ultrafiltration device and ultrafiltration is performed using an ultrafiltration membrane with a molecular weight cutoff of 30 kDa. During the ultrafiltration process, deionized water is added for washing until the content of free polyethyleneimine in the permeate no longer changes significantly. The ultrafiltration retentate is collected, and its solid content is adjusted to give it the fluidity required for subsequent interfacial assembly, resulting in a flame-retardant core dispersion with a polyamine inner layer.

[0063] Step 4, Construction of the alginate outer layer: Weigh 1 part by mass of sodium alginate and add it to deionized water. Stir at room temperature until completely dissolved to prepare a 1% sodium alginate aqueous solution. Adjust the pH of the dispersion obtained in Step 3 to 9.5 ± 0.3. Under shear stirring conditions of 800-1200 r / min, slowly add the sodium alginate aqueous solution over 30-60 min. After the addition is complete, adjust the stirring speed to 400-600 r / min and continue stirring for 90 min to allow the sodium alginate to assemble on the surface of the polyamine inner layer, resulting in a phosphorus-nitrogen flame-retardant dispersion with a mass ratio of 100:0.5:1 for the phosphorus-nitrogen flame-retardant core, polyamine inner layer, and alginate outer layer. According to the subsequent spinning requirements, adjust the solid content and flowability of the dispersion with deionized water and control its pH at 9.0-10.0.

[0064] Step 5, Compounding of the Dispersion and Viscose Forming Solution: After the viscose forming solution has matured and before the final filtration, add the phosphorus-nitrogen flame-retardant dispersion obtained in Step 4. Based on 100 parts by weight of the oven-dry cellulose in the viscose forming solution, the amount of phosphorus-nitrogen flame-retardant core added is 15 parts by weight. During the addition process, maintain the viscose forming solution at 20-25°C. First, add the phosphorus-nitrogen flame-retardant dispersion continuously at a low flow rate, then stir and mix for 60 minutes to ensure the core-shell particles are uniformly dispersed in the viscose forming solution. After mixing, perform vacuum degassing and filter through the final filtration device to obtain the flame-retardant viscose spinning solution.

[0065] Step Six, Wet Forming: The flame-retardant viscose spinning solution is extruded into a coagulation bath through a spinneret. The coagulation bath contains 100 g / L sulfuric acid, 300 g / L sodium sulfate, and 10 g / L zinc sulfate, and the temperature is maintained at 45 ± 2℃. The nascent fibers formed by coagulation are drawn, then sequentially washed, desulfurized, washed again, and dried to obtain flame-retardant cellulose fibers.

[0066] Example 6 Step 1: Preparation of the phosphorus-nitrogen flame retardant core dispersion: Weigh 100 parts by mass of melamine phosphate, 200 parts by mass of deionized water, and 2 parts by mass of fatty alcohol polyoxyethylene ether nonionic dispersant. Dissolve the dispersant in the deionized water beforehand, and then add the melamine phosphate in batches while stirring. After the addition is complete, continue pre-dispersing for 30 minutes to form a uniform slurry. Send the slurry into a high-pressure homogenizer, and control the material temperature at 25±5℃ under circulating cooling conditions. Circulate the material several times under a pressure of 60MPa until the particle size D50 is 0.1~0.5μm and D90 is no greater than 1.5μm, thus obtaining the phosphorus-nitrogen flame retardant core dispersion.

[0067] Step 2, Construction of the polyamine inner layer: Adjust the pH of the phosphorus-nitrogen flame retardant core dispersion to 9.0±0.2 using a dilute sodium hydroxide aqueous solution. Prepare a 15% (w / w) aqueous solution with 8 parts by mass of polyallylamine (weight average molecular weight approximately 15,000). Add the solution dropwise to the phosphorus-nitrogen flame retardant core dispersion over 30-40 minutes while stirring at 500-800 rpm. Maintain the system temperature at 20-25℃ and the pH at 8.8-9.2 during the dropwise addition. After the dropwise addition is complete, continue stirring for 90 minutes to allow the polyallylamine to adsorb onto the surface of the melamine phosphate particles.

[0068] Step 3, Removal of Free Polyamine: The dispersion obtained in Step 2 is introduced into an ultrafiltration device and ultrafiltration is performed using an ultrafiltration membrane with a molecular weight cutoff of 30 kDa. During the ultrafiltration process, deionized water is added for washing until the content of free polyallylamine in the permeate no longer changes significantly. The ultrafiltration retentate is collected and its solid content is adjusted to obtain a flame-retardant core dispersion with a polyamine inner layer.

[0069] Step 4, Construction of the alginate outer layer: Weigh 15 parts by mass of potassium alginate, add it to deionized water, and stir at room temperature until completely dissolved to prepare a 3% potassium alginate aqueous solution. Adjust the pH of the dispersion obtained in Step 3 to 9.5±0.3, and slowly add the potassium alginate aqueous solution over 45-60 minutes under shear stirring conditions of 1000-1500 r / min. After the addition is complete, adjust the stirring speed to 400-600 r / min and continue stirring for 120 minutes to allow the potassium alginate to assemble on the surface of the polyamine inner layer, resulting in a phosphorus-nitrogen flame-retardant dispersion with a mass ratio of 100:8:15 for the phosphorus-nitrogen flame-retardant core, polyamine inner layer, and alginate outer layer. According to the subsequent spinning requirements, adjust the solid content and flowability of the dispersion with deionized water and control its pH at 9.0-10.0.

[0070] Step 5, Compounding of the Dispersion and Viscose Forming Solution: After the viscose forming solution has matured and before the final filtration, add the phosphorus-nitrogen flame-retardant dispersion obtained in Step 4. Based on 100 parts by weight of the oven-dry cellulose in the viscose forming solution, the amount of phosphorus-nitrogen flame-retardant core added is 15 parts by weight. During the addition process, maintain the viscose forming solution at 20-25°C and stir for 90 minutes to ensure the core-shell particles are uniformly dispersed in the viscose forming solution. After mixing, perform vacuum degassing and filter through the final filtration device to obtain the flame-retardant viscose spinning solution.

[0071] Step Six, Wet Forming: The flame-retardant viscose spinning solution is extruded into a coagulation bath through a spinneret. The coagulation bath contains 100 g / L sulfuric acid, 300 g / L sodium sulfate, and 10 g / L zinc sulfate, and the temperature is maintained at 45 ± 2℃. The nascent fibers formed by coagulation are drawn, then sequentially washed, desulfurized, washed again, and dried to obtain flame-retardant cellulose fibers.

[0072] Example 7 Step 1: Preparation of the phosphorus-nitrogen flame-retardant core dispersion: Weigh 100 parts by weight of melamine-coated ammonium polyphosphate (prepared by high-speed mixing of ammonium polyphosphate and melamine at a mass ratio of 95:5), 200 parts by weight of deionized water, and 1 part by weight of polyvinylpyrrolidone. Dissolve the polyvinylpyrrolidone in the deionized water beforehand, and then add the melamine-coated ammonium polyphosphate in batches while stirring. After the addition is complete, continue pre-dispersing for 30 minutes to form a uniform slurry. Feed the slurry into a wet grinding machine and grind it under circulating cooling conditions, controlling the material temperature at 25±5℃, until the particle size D50 is 0.1~0.5μm and D90 is not greater than 1.5μm, thus obtaining the phosphorus-nitrogen flame-retardant core dispersion.

[0073] Step 2, Construction of the polyamine inner layer: Adjust the pH of the phosphorus-nitrogen flame retardant core dispersion to 9.0±0.2 using a dilute sodium hydroxide aqueous solution. Prepare a 10% (w / w) aqueous solution with 4 parts by mass of polyamide amine (weight average molecular weight approximately 5000). Add the solution dropwise to the phosphorus-nitrogen flame retardant core dispersion over 25-35 minutes while stirring at 500-800 rpm. Maintain the system temperature at 20-25℃ and the pH at 8.8-9.2 during the dropwise addition. After the dropwise addition is complete, continue stirring for 60 minutes to allow the polyamide amine to adsorb onto the surface of the flame retardant core.

[0074] Step 3, Removal of Free Polyamine: The dispersion obtained in Step 2 is introduced into an ultrafiltration device and ultrafiltration is performed using an ultrafiltration membrane with a molecular weight cutoff of 30 kDa. During the ultrafiltration process, deionized water is added for washing until the content of free polyamine in the permeate no longer changes significantly. The ultrafiltration retentate is collected and its solid content is adjusted to obtain a flame-retardant core dispersion with a polyamine inner layer.

[0075] Step 4, Construction of the alginate outer layer: Weigh 8 parts by mass of sodium alginate and add it to deionized water. Stir at room temperature until completely dissolved to prepare a 2% sodium alginate aqueous solution. Adjust the pH of the dispersion obtained in Step 3 to 9.5 ± 0.3. Under shear stirring conditions of 800-1200 r / min, slowly add the sodium alginate aqueous solution over 30-60 min. After the addition is complete, adjust the stirring speed to 400-600 r / min and continue stirring for 90 min to allow the sodium alginate to assemble on the surface of the polyamine inner layer, resulting in a phosphorus-nitrogen flame-retardant dispersion with a mass ratio of 100:4:8 for the phosphorus-nitrogen flame-retardant core, polyamine inner layer, and alginate outer layer. Adjust the solid content and flowability of the dispersion with deionized water and control its pH at 9.0-10.0.

[0076] Step 5, Compounding of the Dispersion and Viscose Forming Solution: After the viscose forming solution has matured and before the final filtration, add the phosphorus-nitrogen flame-retardant dispersion obtained in Step 4. Based on 100 parts by weight of the oven-dry cellulose in the viscose forming solution, the amount of phosphorus-nitrogen flame-retardant core added is 15 parts by weight. Maintain the viscose forming solution at 20-25°C and stir for 60 minutes. After completion, perform vacuum degassing and final filtration to obtain the flame-retardant viscose spinning solution.

[0077] Step Six, Wet Forming: The flame-retardant viscose spinning solution is extruded into a coagulation bath through a spinneret. The coagulation bath contains 100 g / L sulfuric acid, 300 g / L sodium sulfate, and 10 g / L zinc sulfate, and the temperature is maintained at 45 ± 2℃. The nascent fibers formed by coagulation are drawn, then sequentially washed, desulfurized, washed again, and dried to obtain flame-retardant cellulose fibers.

[0078] Example 8 Step 1: Preparation of the phosphorus-nitrogen flame-retardant composite core dispersion: Weigh 90 parts by mass of melamine polyphosphate, 10 parts by mass of α-zirconium phosphate (phosphorus-containing inorganic sheet material), 200 parts by mass of deionized water, and 3 parts by mass of polyvinylpyrrolidone. Dissolve the polyvinylpyrrolidone in the deionized water beforehand, and then add the mixed powder of melamine polyphosphate and α-zirconium phosphate in batches while stirring. After the addition is complete, continue pre-dispersing for 30 minutes to form a uniform slurry. Feed the slurry into a wet grinding equipment and grind it under circulating cooling conditions, controlling the material temperature at 25±5℃, until the D50 of the composite particles is 0.1~0.5μm and the D90 is not greater than 1.5μm, thus obtaining the phosphorus-nitrogen flame-retardant composite core dispersion.

[0079] Step 2, Construction of the polyamine inner layer: Adjust the pH of the phosphorus-nitrogen flame-retardant composite core dispersion to 9.0±0.2 using a dilute sodium hydroxide aqueous solution. Prepare a 10% (w / w) aqueous solution with 6 parts by mass of branched polyethyleneimine, and add it dropwise to the composite core dispersion over 20-30 minutes while stirring at 500-800 rpm. Maintain the system temperature at 20-25℃ and the pH at 8.8-9.2 during the dropwise addition. After the dropwise addition is complete, continue stirring for 60 minutes to allow the branched polyethyleneimine to adsorb onto the surface of the composite particles.

[0080] Step 3, Removal of Free Polyamine: The dispersion obtained in Step 2 is introduced into an ultrafiltration device and ultrafiltration is performed using an ultrafiltration membrane with a molecular weight cutoff of 30 kDa. During the ultrafiltration process, deionized water is added for washing until the content of free polyethyleneimine in the permeate no longer changes significantly. The ultrafiltration retentate is collected and its solid content is adjusted to obtain a composite flame-retardant core dispersion with a polyamine inner layer.

[0081] Step 4, Construction of the alginate outer layer: Weigh 12 parts by mass of sodium alginate, add it to deionized water, and stir at room temperature until completely dissolved to prepare a 2.5% sodium alginate aqueous solution. Adjust the pH of the dispersion obtained in Step 3 to 9.5 ± 0.3, and slowly add the sodium alginate aqueous solution over 30 to 60 minutes under shear stirring conditions of 800 to 1200 r / min. After the addition is complete, adjust the stirring speed to 400 to 600 r / min and continue stirring for 120 minutes to allow the sodium alginate to assemble on the surface of the polyamine inner layer, resulting in a phosphorus-nitrogen flame-retardant dispersion with a mass ratio of 100:6:12 for the phosphorus-nitrogen flame-retardant core, polyamine inner layer, and alginate outer layer. Adjust the solid content and flowability of the dispersion with deionized water and control its pH at 9.0 to 10.0.

[0082] Step 5, Compounding of the Dispersion and Viscose Forming Solution: After the viscose forming solution has matured and before the final filtration, add the phosphorus-nitrogen flame-retardant dispersion obtained in Step 4. Based on 100 parts by weight of the oven-dry cellulose in the viscose forming solution, the amount of phosphorus-nitrogen flame-retardant core added is 15 parts by weight. Maintain the viscose forming solution at 20-25°C and stir for 60 minutes. After completion, perform vacuum degassing and final filtration to obtain the flame-retardant viscose spinning solution.

[0083] Step Six, Wet Forming: The flame-retardant viscose spinning solution is extruded into a coagulation bath through a spinneret. The coagulation bath contains 100 g / L sulfuric acid, 300 g / L sodium sulfate, and 10 g / L zinc sulfate, and the temperature is maintained at 45 ± 2℃. The nascent fibers formed by coagulation are drawn, then sequentially washed, desulfurized, washed again, and dried to obtain flame-retardant cellulose fibers.

[0084] Performance testing: The flame retardant properties of the flame-retardant cellulose fiber prepared in Example 1 were tested, with ordinary viscose fiber used as a control sample.

[0085] (1) The sample was placed under vertical conditions in an oxygen-nitrogen mixed gas flow, and the minimum oxygen concentration required for the sample to just maintain combustion (i.e., limiting oxygen index) was measured. The test results showed that the limiting oxygen index of ordinary viscose fiber was 18.5%, while the limiting oxygen index of flame-retardant cellulose fiber in Example 1 was 30.2%, which was significantly higher than that of ordinary viscose fiber.

[0086] (2) Ignite the center of the bottom edge of the vertical sample with the flame generated by the igniter. After 12 seconds of ignition, remove the flame and record the afterburn time, smoldering time and damage length. The results are shown in Table 1.

[0087] Table 1. Results of Vertical Combustion Test

[0088] As shown in Table 1, the flame-retardant cellulose fiber in Example 1 self-extinguished immediately after the fire source was removed, with both the afterflame time and smoldering time being 0s and the damaged length being 85mm, demonstrating excellent self-extinguishing performance after the fire source was removed.

[0089] (3) Washability, flame retardancy, and elemental retention The fiber products were repeatedly washed according to the applicable washing procedure in GB / T 8629; after washing, they were dried and conditioned, and then the LOI and vertical burning performance were measured. The P and Zn element contents could be determined using ICP-OES or XRF. The flame retardant element retention rate was calculated using the following formula: R=W n / W0×100% Where W0 represents the elemental content before washing, W n The element content after n washes is shown in Table 2. Table 2. Test results of flame retardant and washability properties of flame-retardant cellulose fibers.

[0090] As shown in Table 2, the flame-retardant cellulose fiber prepared in Example 1 maintained a limiting oxygen index of 28.8% and an afterflame time of 0 s after 20 standard washes, with phosphorus and zinc retention rates as high as 88.6% and 84.9%, respectively, demonstrating excellent flame-retardant durability. In contrast, ordinary viscose fiber could not self-extinguish after being removed from the flame, proving that the core-shell structure design of this invention effectively achieves efficient fixation of flame-retardant components within the fiber.

[0091] The above are merely preferred embodiments of the present invention and are not intended to limit the present invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A phosphorus-nitrogen flame retardant dispersion, characterized in that, It includes a continuous aqueous phase and core-shell particles dispersed in the continuous aqueous phase; the core-shell particles, from the inside out, include a phosphorus-nitrogen flame-retardant core, a polyamine inner layer adsorbed on the surface of the phosphorus-nitrogen flame-retardant core, and an alginate outer layer assembled on the surface of the polyamine inner layer.

2. The phosphorus-nitrogen flame retardant dispersion according to claim 1, characterized in that, The mass ratio of the phosphorus-nitrogen flame-retardant core, the polyamine inner layer, and the alginate outer layer is 100:(0.5~8):(1~15).

3. The phosphorus-nitrogen flame retardant dispersion according to claim 1, characterized in that, The material of the phosphorus-nitrogen flame retardant core is melamine polyphosphate, ammonium polyphosphate, melamine phosphate, or ammonium polyphosphate compounded on the surface of melamine; Alternatively, the material of the phosphorus-nitrogen flame-retardant core may be melamine polyphosphate, ammonium polyphosphate, melamine phosphate, or a composite particle formed by ammonium polyphosphate compounded on the surface of melamine and phosphorus-containing inorganic sheet material.

4. The phosphorus-nitrogen flame retardant dispersion according to claim 1, characterized in that, The material of the polyamine inner layer includes one or more of branched polyethyleneimine, linear polyethyleneimine, polyallylamine, and polyamide amine; Alternatively, the material of the inner polyamine layer may be a water-soluble salt of branched polyethyleneimine, linear polyethyleneimine, polyallylamine, or polyamide amine.

5. The phosphorus-nitrogen flame retardant dispersion according to claim 1, characterized in that, The alginate outer shell is made of one or more of sodium alginate and potassium alginate.

6. The method for preparing the phosphorus-nitrogen flame retardant dispersion according to any one of claims 1 to 5, characterized in that, Includes the following steps: The phosphorus-nitrogen flame retardant material, water and dispersant stabilizer are mixed and then subjected to wet grinding or high-pressure homogenization at 5~35℃ to obtain a flame retardant core dispersion containing phosphorus-nitrogen flame retardant cores. The pH of the flame-retardant core dispersion is adjusted to 8.0~10.5, and a polyamine aqueous solution is added under stirring. Stirring is continued to allow the polyamine to be adsorbed onto the surface of the phosphorus-nitrogen flame-retardant material, forming a flame-retardant core dispersion with a polyamine inner layer. The pH of the flame-retardant core dispersion with the polyamine inner layer is maintained at 8.0~11.

0. Under shear conditions, an aqueous alginate solution is added, and stirring is continued to allow the alginate to assemble on the surface of the polyamine inner layer, forming the phosphorus-nitrogen flame-retardant dispersion.

7. The preparation method according to claim 6, characterized in that, The dispersion stabilizer includes one or more of polyvinylpyrrolidone and polyoxyethylene ether nonionic dispersants.

8. The preparation method according to claim 6, characterized in that, The amount of the dispersing stabilizer is 0.1% to 3% of the mass of the phosphorus-nitrogen flame retardant material.

9. A method for preparing flame-retardant cellulose fibers, characterized in that, Includes the following steps: The phosphorus-nitrogen flame retardant dispersion according to any one of claims 1 to 5 is mixed with an alkaline cellulose spinning solution to obtain a flame retardant spinning solution; The flame-retardant spinning solution is extruded into a coagulation bath containing acid and divalent metal ions, so that the cellulose in the alkaline cellulose spinning solution is coagulated and regenerated to obtain nascent fibers. The nascent fibers are stretched, washed, and dried to obtain flame-retardant cellulose fibers.

10. Flame-retardant cellulose fiber prepared by the preparation method according to claim 9.